Analisis Efektivitas Biaya Pengobatan Hipertensi Dan Diabetes Melitus Di Rumah Sakit Efarina Ataham Pangkalan Kerinci - Meyana Marbun; Marolop Parlindungan Napitu; Hendri Kurniawan; Ismi Noer Fadilah; Muliti Muliti (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2021)
Hypertension is a condition in which blood pressure increases above (≥140/90 mmHg). The prevalence in Indonesia is 32.2% and only 24.2% of these hypertensive patients are diagnosed and receiving treatment. Diabetes mellitus (DM) is a metabolic disorder characterized by glucose levels exceeding normal values or perglycemia (≥200 mg/dl). to evaluate the cost-effectiveness of antihypertensive and anti-diabetic in patients who are hospitalized at Efarina Etaham Berastagi Hospital, Karo. This research is non-experimental using data taken from patient medical records retrospectively for the period January-June 2017. The analytical method used is Cost Effectiveness Analysis (CEA). The Cost Effectiveness Average Ratio (CEA Ratio) and Incremental Cost Effectiveness Ratio (ICER) methods were used to analyze the most cost-effective antihypertensives and antidiabetics. The results of this study showed that the hypertension therapy regimens used were amlodipine, captropil, valsartan, amlodipine + captropil, amlodipine + valsartan, captorpil + valsartan, and amlodipine + captorpil + valsartan. In the anti-diabetic therapy regimen used are insulin analogues, metmorphine and insulin analogues + metmorphine. The most cost-effective antihypertensive based on the CEA and ICER is amdolpine + captropil and the most cost-effective diabetic liver based on the CEA and ICER is metmorphine.